2004
DOI: 10.3354/dao061241
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics, infestation and host selection of Vexilla vexillum, an ectoparasitic muricid of echinoids, in Madagascar

Abstract: The symbiotic interaction, population and infestation dynamics of the muricid Vexilla vexillum (Gmelin, 1791) on 2 echinoid species, Tripneustes gratilla (Linnaeus, 1785) and Echinometra mathaei (Blainville, 1825), was investigated on the barrier reef off Toliara (Madagascar). V. vexillum is an ectoparasitic muricid which was exclusively found in association with sea urchins, on which it moves freely and browses over the integument. Host recovery from damage caused by muricid grazing was dependent on lesion s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Infections then progress through the test, often causing fatal perforations (Vaïtilingon et al 2004). The present study examines this infection that leads to the death of T. gratilla.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
See 2 more Smart Citations
“…Infections then progress through the test, often causing fatal perforations (Vaïtilingon et al 2004). The present study examines this infection that leads to the death of T. gratilla.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…A recent survey on the southwest coast of Madagascar (off Toliara) revealed the presence of the parasitic gastropod Vexilla vexillum on 2 echinoid species, Tripneustes gratilla and Echinometra mathaei (Vaïtilingon et al 2004). The gastropod is always found associated with these echinoids and is never observed free-living.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These organisms are primarily carnivores (Abe, 1980(Abe, , 1983Carriker, 1981;Hughes, 1986;Harper and Morton, 1994;Navarette, 1996), however several species have evolved other modes of feeding such as omnivory, scavenging (Keable, 1995;Tsuchiya, 2000), detritivory (Vermeij and Carlson, 2000), parasitism (Vaïtilingon et al, 2004), corallivory (Taylor, 1983;Boucher, 1986;Turner, 1994), and even herbivory (Vermeij and Carlson, 2000;Kantor, 2002). Most species are seasonal spawners (Yamamoto, 1997) and deposit large aggregates of egg masses to avoid predation.…”
Section: Introductionmentioning
confidence: 99%
“…Although they suggested that tissue adhesion is a fourth type of adhesion, we rather propose that this is a sub-category of either permanent, transitory or temporary adhesion, that should be opposed to adhesion to abiotic substrata. Indeed, examples of tissue adhesion include permanent attachment of parasitic barnacles on whale skin (Ridgway et al 1997), transitory attachment of parasitic gastropods on echinoderm epidermis (Vaitilingon et al 2004), or temporary attachment of parasitic monogeneans on the gills or skin of fishes (Whittington and Cribb 2001). There are, however, invertebrate adhesive systems that do not fit into the three types of adhesion described above.…”
Section: Introductionmentioning
confidence: 99%